The RACK1 signaling scaffold protein selectively interacts with Yersinia pseudotuberculosis virulence function. - Sara E Thorslund; Tomas Edgren; Jonas Pettersson; Roland Nordfelth; Mikael E Sellin; Ekaterina Ivanova; Matthew S Francis; Elin L Isaksson; Hans Wolf-Watz; Maria Fällman (PLoS ONE, 2011)
Many gram-negative bacteria use type III secretion systems to translocate effector proteins into host cells. These effectors interfere with cellular functions in a highly regulated manner resulting in effects that are beneficial for the bacteria. The pathogen Yersinia can resist phagocytosis by eukaryotic cells by translocating Yop effectors into the target cell cytoplasm. This is called antiphagocytosis, and constitutes an important virulence feature of this pathogen since it allows survival in immune cell rich lymphoid organs. We show here that the virulence protein YopK has a role in orchestrating effector translocation necessary for productive antiphagocytosis. We present data showing that YopK influences Yop effector translocation by modulating the ratio of the pore-forming proteins YopB and YopD in the target cell membrane. Further, we show that YopK that can interact with the translocators, is exposed inside target cells and binds to the eukaryotic signaling protein RACK1. This protein is engaged upon Y. pseudotuberculosis-mediated β1-integrin activation and localizes to phagocytic cups. Cells with downregulated RACK1 levels are protected from antiphagocytosis. This resistance is not due to altered levels of translocated antiphagocytic effectors, and cells with reduced levels of RACK1 are still sensitive to the later occurring cytotoxic effect caused by the Yop effectors. Further, a yopK mutant unable to bind RACK1 shows an avirulent phenotype during mouse infection, suggesting that RACK1 targeting by YopK is a requirement for virulence. Together, our data imply that the local event of Yersinia-mediated antiphagocytosis involves a step where YopK, by binding RACK1, ensures an immediate specific spatial delivery of antiphagocytic effectors leading to productive inhibition of phagocytosis.